THE SEMIOTICS OF BANYAN TREE SPACES IN DENPASAR, BALI - I Kadek Merta Wijaya (International Journal on Livable Space, 2019)
ABSTRACT The concept of Banyan space (spaces under Banyan tree) possesses both secular and ritual values. Secular values are related to the use of space for socio-economic activities, such as trading to others and meeting with friends. Ritual values are related to activities that take place around the Banyan tree as an expression of belief on the tree’s “tenget” (sacred) values. Secular and ritual values create the concept of space on Banyan tree, based on the elements of space and the conception used of these spaces. A system of signs (signifier and signified) mark the values or meanings of “sekala” and “niskala” space. This research aims to find out the elements that create the “sekala” and “niskala” space by analysing the space system of signifier and signified. “Sekala” is tangible or visible space which can be perceived by five senses. “Niskala” is intangible or invisible space, yet it exists and Balinese Hindus believe in its presence. The research focuses on the system of activities from selected cases by purposive sampling using qualitative naturalistic method and approach. The results of this research emphasize that (1) there are elements (signifier and signified) that create the “sekala” and “niskala” space and (2) there are normative and scientific concepts of Banyan trees as the background for the creation of the “sekala” and niskala space. Keywords: sekala space, niskala space, secular and ritual values, signifier and signified space